2020
DOI: 10.1017/s1755048320000644
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Religious Politicking? An Analysis of 24 Democratic Elections

Abstract: Why do clergy talk with congregants about elections to a greater extent in Mozambique than Indonesia, or in the United States than Taiwan? Arguing that context shapes religious actors' micro-level incentives to discuss or avoid electoral politics, we seek to explain variation in religious politicking—religious leaders' and organizations' engagement in electoral campaigns. Our framework integrates individual-level and country-level approaches, as well as theories of modernization, secularism, and religious comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Some of these studies only analysed the effects of religious competition in Latin American countries (Froehle 1994; Gill 1994, 1998; Smith 2016; Trejo 2009), arguing that Catholic churches took liberal stances because of religious competition with Protestants – to prevent conversions to the competing religion. A few have developed these dynamics in democratic countries (Djupe and Neiheisel 2019; Monsma and Soper 2009; Rosenberg and Smith 2021), where they found that the political goods that the churches provide are directed to attract new members and retain the current ones. Karrie Koesel (2015) assessed the religious economy approach in Russia and China, where her study revealed similar political dynamics under heavy market constraints.…”
Section: Religion In Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies only analysed the effects of religious competition in Latin American countries (Froehle 1994; Gill 1994, 1998; Smith 2016; Trejo 2009), arguing that Catholic churches took liberal stances because of religious competition with Protestants – to prevent conversions to the competing religion. A few have developed these dynamics in democratic countries (Djupe and Neiheisel 2019; Monsma and Soper 2009; Rosenberg and Smith 2021), where they found that the political goods that the churches provide are directed to attract new members and retain the current ones. Karrie Koesel (2015) assessed the religious economy approach in Russia and China, where her study revealed similar political dynamics under heavy market constraints.…”
Section: Religion In Transitionsmentioning
confidence: 99%
“…These tangible and intangible goods are used for political mobilizations that could serve the interests of the government or the opposition. For example, the direct engagement by religious actors in elections, known as ‘religious politicking’, is when religious institutions engage with civil society groups to observe the elections and campaign for a candidate during religious services (Rosenberg and Smith 2021: 737–738).…”
Section: Religious Competition Regulation and The Market For Legitimacymentioning
confidence: 99%